Surgical Management of Gallstone Ileus in Low-Settings Hospital during COVID-19 Outbreak: A Case Report - Al-Abbasi, Ghaith; Alhilfy, Ali Adil; Al-Jasim, Ameer (The Surgery Journal, 2021)
Introduction Gallstone ileus is a very infrequent complication of cholelithiasis in which single or multiple stones pass through an abnormal fistula to the lumen of the intestine leading to a true mechanical obstruction. We are reporting a case of a female who developed intestinal obstruction due to gallstones during the coronavirus disease 2019 (COVID-19) outbreak and was managed urgently surgically in a low-settings hospital.Case Presentation An 85-year-old white female with 40 years history of gallstone disease, hypertension, and type-2 diabetes presented to the accidents and emergency unit with upper central crampy abdominal pain for 5 days associated with green color vomiting and absolute constipation. On examination, she was barely stable, dehydrated, had a distended abdomen, and guarding in the epigastric region. Her electrolytes were disturbed and had elevated serum creatinine and blood urea. Imaging studies confirmed gallstone ileus. Management was surgical despite the lack of facilities and equipment including COVID-19 personal protective equipment.Conclusion Despite being an infrequent complication, gallstone ileus might present at the most unexpected time and in the least equipped hospital where the surgeon's suspicion, risk stratification, and improvisation by utilizing what is available are the keys for successful management and saving lives.
Keywords: surgical management; gallstone ileus; COVID-19; low-settings hospital; case report